Maternal exposure to GOS/inulin mixture prevents food allergies and promotes tolerance in offspring in mice. Issue 1 (26th October 2015) - Bouchaud, G.; Castan, L.; Chesné, J.; Braza, F.; Aubert, P.; Neunlist, M.; Magnan, A.; Bodinier, M.
Abstract: Background: Food allergies affect 4–8% of children and are constantly on the rise, thus making allergies a timely issue. Most importantly, prevention strategies are nonexistent, and current therapeutic strategies have limited efficacy and need to be improved. One alternative to prevent or reduce allergies, particularly during infancy, could consist of modulating maternal immunity and microbiota using nondigestible food ingredients, such as prebiotics. For this purpose, we studied the preventive effects of prebiotics in Balb/c mothers during pregnancy and breastfeeding on food allergy development in offspring mice. Methods: After weaning, the offspring from mothers that were exposed to GOS/inulin mixture or fed a control diet were intraperitoneally sensitized to wheat proteins to induce a systemic allergic response and orally exposed to the same allergen. Immunological, physiological, and microbial parameters were analyzed. Results: GOS/inulin mixture diet modified the microbiota of mothers and their offspring. Offspring from mothers that received GOS/inulin prebiotics were protected against food allergies and displayed lower clinical scores, specifically of IgE and histamine levels, compared to offspring from mothers fed a control diet. Moreover, GOS/inulin supplementation for the mother resulted in stronger intestinal permeability in the offspring. Enhancement of the regulatory response to allergic inflammation and changes in the Th2/Th1 balance toward a dampened Th2 response were observed in mice from GOS/inulin mixture‐exposed mothers. Conclusion: The treatment of pregnant and lactating mice with nondigestible GOS/inulin prebiotics promotes a long‐term protective effect against food allergies in the offspring.